The Role of Technology in The Representation of The True People in Nano Riantiarno's Performance of The Demonstrator Play - Devitalisa M, Wulan; Munaris, Munaris; Widodo, Mulyanto; Sumarti, Sumarti; Samhati, Siti (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This research discusses the role of technology in the representation of the true people in Nano Riantiarno's play "Demonstran". Using Roland Barthes' semiotic approach, this research aims to identify signs that represent the true people in the context of the play. Through digital media, elements such as stage settings, costumes, visual settings, music, background sounds, and sound effects are used to strengthen the representation of the people. This research explores how technology affects the way folk representations are understood and received by the audience. As such, it contributes to the understanding of the relationship between technology, semiotics and folk representation in the context of performing arts.